Analysis of orbital configurations for Millimetron space observatory. (July 2022) - Rudnitskiy, A.G.; Mzhelskiy, P.V.; Shchurov, M.A.; Syachina, T.A.; Zapevalin, P.R.
Abstract: In this contribution a primary feasibility study of different orbital configurations for Millimetron space observatory is presented. Priority factors and limitations were considered by which it is possible to assess the capabilities of a particular orbit. It included technical and scientific capabilities of each orbit regarding the fuel costs, satellite observability, the quality of very long baseline interferometric (VLBI) imaging observations and source visibilities. Highlights: The best orbit for Millimetron observatory is an orbit around the Sun–Earth L2 point. Suggested a new family of L2 orbits as nominal for the Millimetron observatory. Estimated (u, v) coverage shows VLBI imaging observations are possible in L2 orbit. HEO orbits have a potential to perform the transfer to/from the L2 point. Optimizing L2 point orbit is more practical than developing a two-stage VLBI mission.